Exploring the role of academic heads in maintaining the quality of teaching and learning within their departments: A case study of a private university - Tumar, Annyza; Asimiran, Soaib; Lope Pihie, Zaidatol Akmaliah; Ismail, Ismi Arif (Sakarya University, 2016)
Higher education institutions are generally concern with the quality of their graduates. Many institutions put in a lot effort in ensuring quality teaching and learning experience to their students because this reflection on the quality of the institutions themselves. This paper report the findings a qualitative case study at a Malaysian private university. It explores the meaning of the quality teaching and learning, from the perspectives of academics and their head departments. It also reviews the roles of the head of departments in maintaining the quality of teaching and learning within their departments. Findings indicate that head of departments play a very important role in three in areas: 1. assessing the quality of teaching and learning, 2. identifying academic staff development needs; 3. supporting continues professional development activities within the departments. In addition, in effort to improve the quality of their teaching, academics were found to be more satisfied with professional development activities at department level than activities carried out at institutional level. The paper concludes with suggestion on strategies for enhancing professional development opportunities for improving teaching and learning within the departments and institutional itself.